Intersection between integrative and complementary practices in the field of health and ecology of knowledge (Research, Society and Development, 2023)
The objective of the study is to identify the intersection between integrative and complementary practices in the field of health and ecology of knowledge. The present study is an integrative literature review, this methodology has as its main purpose to generate a synthesis of how the results were acquired in the research. The elaboration of a methodological survey for the research was carried out in the period of December 2022, the databases used were the Latin American and Caribbean Literature in Health Sciences, Database in Nursing and Medical Literature Analysis and a Retrievel System Online, using the Health Sciences Descriptors, namely “Complementary Therapies”, “Mental Health” and “Public Health”, through the Boolean AND operator. A quantitative of ten articles was selected to compose the analysis corpus. There is a link between cultural practices, the identity issue and health care, for example, when you approach technical knowledge with people in the community on a certain subject, they not only learn knowledge, but also teach knowledge acquired throughout life, thus transforming it into a teaching-learning process The potential and need for dialogue between traditional knowledge and scientific knowledge is well known, and this is not restricted to issues related to health. It is important to emphasize that, even with the knowledge of the hegemony imposed by scientific knowledge, this should not be disregarded, because, according to the studies, each knowledge in the light of the ecology of knowledge has its degree of importance.